Investment decisions under hidden competition - Pereira, Paulo Jorge (2013)
We present a model adequate for investment decisions in duopolies under total hidden competition. In this competitive context all potential entrants remain unrevealed until they decide to move into the market. The value-functions and the optimal entry thresholds are derived.